"Other Fields Are More Lucrative and Sexy": A Qualitative Examination of the Low Number of Men in Psychology. (April 2021) - Beasley, Samuel T.; Sánchez, Berenice; Butler, Maime; Chapman-Hilliard, Collette
While the underrepresentation of women in traditionally masculine fields has received much scholarly attention, less work has examined men's lower numbers in women majority fields. Additionally, much of the available research on men in these fields is limited to a few vocations (e.g., nursing and teaching). Expanding career-related research on men in other women majority fields allows for more targeted career interventions with young boys and men as they are making career decisions in a service-oriented economy. The current study focuses on men in psychology ( N = 210) to examine factors that contribute to the low number of men in this women majority field. Using consensual qualitative research–modified, four domains were identified that may help explain the paucity of men in psychology: professional psychology issues, socialization, financial factors, and broader changes in higher education. Implications of these findings for career practice and research with boys and men are discussed.